Who was Albert Einstein? - Brallier, Jess M.; Parker, Robert Andrew (New York : Grosset & Dunlap, 2002)
Tells the life story of history-making physicist Albert Einstein, describing his beginnings as a scientist, his experiences in Nazi Germany, his arrival in the U.S., and his major accomplishments, and includes a chronology.
5.8
3-6
3-6
Keywords: Einstein, Albert, -- 1879-1955 -- Juvenile literature; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955.; Physicists -- United States -- Biography -- Juvenile literature; Scientists -- United States -- Biography -- Juvenile literature; Physicists; Scientists; Physicists -- United States -- Biography; Scientists -- United States -- Biography